A covalent organic framework-catalyzed visible-light-induced three-component cascade synthesis of trifluoroalkyl and trifluoroalkenyl quinoxalin-2(1H)-one derivatives. (17th October 2022) - Wang, Hesheng; Li, Siyu; Cui, Yue; Liu, Minqiang; Bu, Xiubin; Tian, Hua; Yang, Xiaobo
Abstract : A COF-catalyzed visible-light-induced three-component synthesis of trifluoroalkyl and trifluoroalkenyl quinoxalin-2(1 H )-one derivatives features robust substrate adaptability, good sustainability, and Z -selectivity. Abstract : Herein, we report a visible-light-induced three-component cascade reaction of alkenes or alkynes with CF3 SO2 Na and quinoxalin-2(1 H )-one derivatives. In this reaction, a photoactive two-dimensional imine-linked covalent organic framework (2D-COF-5) was employed as the heterogeneous photocatalyst. Benefiting from the excellent photoactivity, stability, and inherent heterogeneous nature of 2D-COF-5, this visible-light-induced three-component cascade reaction occurred smoothly in a selective, green, and sustainable manner. A wide range of C3 trifluoroalkyl and trifluoroalkenyl quinoxalin-2(1 H )-one derivatives were produced in satisfying yields. A preliminary investigation of the reusability for 2D-COF-5 demonstrated the good maintenance of photocatalytic performance, basic chemical structure, and micro-appearance in eight recycling runs.